STRATEGI PENGEMBANGAN BISNIS PETERNAKAN LEMBU DAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PARA PETERNAK LEMBU DI GAMPONG LHOKJOK, KABUPATEN ACEH UTARA - Sufrizal; Maulina, Isra; Husna Hayati; Heny Rofizar; Juliana Putri (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
This community service is aimed at assisting the development strategy of cattle farming; and Partners can understand about capital planning, capital management and preparation of bull financial reports. The method used in this service activity is the lecture method, training method and demonstration. Methods Training and demonstration on this occasion Community Service Team provided training and demonstrations on capital management and planning, financial reporting and the tools needed to make financial reports. While the method of obtaining financial data in this Service Activity was found by the Community Service Team in the form of questions and answers and discussions with cattle training participants in Gampong Lhokjok Kecamatan Kutamakmur. The results of community service show that (1) The development of the beef cattle business in Lhokjok Village is still low, so a market mix strategy is needed, namely 4 p (product, price, place and promotion) as well as accelerating the cattle breeding and fattening business. Through breeding and fattening business activities, there will be the distribution of superior breeds of productive broiler cattle. as well as increasing the income and welfare of breeders. Efforts to increase the population of beef cattle through improvement of productive male and female breeds can be carried out by means of IB and natural mating. (2) The preparation of financial statements for cattle Gampong Lhokjok breeders is still very traditional, so a simple financial arrangement is needed, by compiling a cash in and cash out book, a purchase and sale book, an accounts payable book, and income statement.